The Effect of Environmental Disclosure on the Cost of Capital for Environmentally Sensitive Industrial Companies - Naufal Daniswara Putra Wahono; Wuryan Andayani (Journal of Social Research, 2026)
The cost of capital is an important aspect of a company's financial decision-making because it reflects the rate of return required by investors and creditors to compensate for the risks they undertake. In the context of increasing attention to sustainability issues, environmental disclosure has emerged as a non-financial factor that may influence investors' risk perceptions and, consequently, the cost of capital. This study aims to examine the effect of environmental disclosure—voluntary disclosure based on the Global Reporting Initiative (GRI) Standards and mandatory disclosure under SEOJK No. 16/SEOJK.04/2021—on the cost of capital of environmentally sensitive industrial companies listed on the Indonesia Stock Exchange. The study used secondary data obtained from annual reports and sustainability reports and employed a quantitative correlational research design. The data were analyzed using multiple linear regression based on 99 company-year observations. The sample was selected using a combination of quota sampling and purposive sampling. The results showed that voluntary environmental disclosure had a positive and statistically significant effect on the cost of capital, whereas mandatory environmental disclosure had a positive but statistically insignificant effect. Firm size had a negative but statistically insignificant effect on the cost of capital. These findings indicate the existence of a trade-off in environmental disclosure, whereby greater transparency does not necessarily reduce the cost of capital unless it is accompanied by credibility and the expectation of long-term economic benefits.